Knowledge, Attitude, and Practice of Palliative Care Among Physicians and Nurses in Intensive Care Units in Shanghai, China - He X; Cai H; Zhang J; Chen W; Zhu B (Journal of Multidisciplinary Healthcare)
Xinhe He,1,2,* Hengzhe Cai,3,* Jingying Zhang,4,* Wei Chen,1 Biao Zhu1 1Department of Anaesthesia, Critical Care and Pain Medicine, Fudan University Shanghai Cancer Center, Shanghai, 200032, People’s Republic of China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, 200032, People’s Republic of China; 3High School Affiliated to Fudan University, Shanghai, 200433, People’s Republic of China; 4Nursing Department, Fudan University Shanghai Cancer Center, Shanghai, 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Biao Zhu, Department of Anaesthesia, Critical Care and Pain Medicine, Fudan University Shanghai Cancer Center, No. 270, Dongan Road, Shanghai, 200032, People’s Republic of China, Tel +86-13681971629, Email zhubiaozs@126.com Wei Chen, Department of Anaesthesia, Critical Care and Pain Medicine, Fudan University Shanghai Cancer Center, No. 270, Dongan Road, Shanghai, 200032, People’s Republic of China, Email chenwei_fdu@fudan.edu.cnPurpose: The growing need for palliative care in China’s aging population highlights the intensive care unit (ICU) staff’s crucial role and need for specialized training and improved knowledge, attitude, and practice (KAP). The study aims to assess the KAP of palliative care ICU physicians and nurses and identify influencing factors.Patients and Methods: A cross-sectional survey was conducted among ICU physicians and nurses at three Shanghai hospitals. A self-developed structured online questionnaire was used to collect participant characteristics and KAP data related to palliative care. Pathway analysis explored associations among knowledge, attitude, and practice.Results: Among 203 participants, median scores for knowledge, attitude, and practice were 8/18, 39/50, and 35/45, respectively. Multivariable analysis revealed that 10– 15 years (OR=0.06) and > 15 years (OR=0.19) of experience in the ICU and the lack of palliative care experience (OR=0.29) were associated with poor knowledge. Positive attitudes (OR=1.22) and palliative care training (OR=3.25) were associated with proactive practice. Knowledge directly impacted attitude (β=0.260; P=0.012) and practice (β=0.320, P< 0.001), while attitude directly influenced practice (β=0.278, P< 0.001).Conclusion: The study reveals a low KAP level of palliative care among ICU physicians and nurses in Shanghai. Pathway analysis underscores the crucial role of knowledge in shaping attitudes and practices, emphasizing the urgency of improving knowledge and attitudes toward palliative care among physicians and nurses.Keywords: palliative care, intensive care unit, physicians, nurses, knowledge, attitude, practice